2017
DOI: 10.1007/s10495-017-1381-3
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin protects human umbilical vein endothelial cells from injury through ERK and Akt mediated Nrf2/HO-1 signaling pathway

Abstract: Atherosclerosis-related cardiovascular disease is the predominant cause of death worldwide. Ox-LDL-induced vascular endothelial cell injury is a major factor in the pathogenesis of atherosclerosis. Dihydromyricetin (DMY) is a flavonoid extracted from vine tea that exerts multiple pharmacological activities, including cardio-protective, anti-tumor, and anti-oxidative effects. However, it is unreported that DMY shows protective effects on ox-LDL-induced endothelial cell injury. In this study, we used an ox-LDL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 47 publications
1
41
2
Order By: Relevance
“…Thus, inhibition of high oxidative reactive species production can alleviate the I/R-induced damage. Importantly, activation of Nrf2/HO-1 signaling plays an important role in the inhibition of DNA damage and cell apoptosis by modulating oxidative stress [25,26]. There is evidence showing that inhibition of miR-153 protects neurons against oxygen-glucose deprivation and reoxygenation (OGD-R)induced injury by regulating Nrf2/HO-1 signaling [21].…”
mentioning
confidence: 99%
“…Thus, inhibition of high oxidative reactive species production can alleviate the I/R-induced damage. Importantly, activation of Nrf2/HO-1 signaling plays an important role in the inhibition of DNA damage and cell apoptosis by modulating oxidative stress [25,26]. There is evidence showing that inhibition of miR-153 protects neurons against oxygen-glucose deprivation and reoxygenation (OGD-R)induced injury by regulating Nrf2/HO-1 signaling [21].…”
mentioning
confidence: 99%
“…Qin's research showed that DMY attenuated atherosclerosis through the Nrf2 signalling pathway and induced HUVEC apoptosis . Luo's found that DMY protects HUVECs from ox‐LDL‐induced oxidative injury by activating Nrf2/HO‐1 pathway by up‐regulating Akt and ERK1/2 . Zeng's study showed that DMY reduce foam cell formation via activation of LXRα‐ABCA1/ABCG1 signalling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, 400 μL 1 × binding buffer was added and vortex briefly. The number of apoptotic cells was analysed using a flow cytometry as previously described …”
Section: Sod and Mdamentioning
confidence: 99%
See 2 more Smart Citations